Peran Advokasi Dan Komunikasi Dalam Program Kelurahan Tangguh Bencana Kota Bengkulu - Yuliani, Hafri; Widarini, Dwi Ajeng; Ayuh, Eceh Trisna (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2024)
This study aims to analyze the Role of Advocacy and Communication in the Disaster Resilient Village/Sub-district Program (DESTANA) in Bengkulu City. The method used in this study is a qualitative method, data collection techniques: observation by observing DESTANA activities in Bengkulu City, and interviewing the elements involved. Research Results: first, communicating disaster risks through the formation of a DRR forum and the use of social media such as Instagram, conventional media such as radio, bulletins, pamphlets and brochures and news in online media. second, the process of disseminating information about disasters occurs between communicators in this case (Regional facilitators, Village/Sub-district Facilitators) to the DRR Forum of each sub-district which is the DESTANA Implementation Center. third, the dialogue process occurs during the coordination meeting between the Deputy Coordinator, Regional Facilitator, Village/Sub-district Facilitator with Regional Apparatus Organizations (OPD) such as the Social Service, PMD Service, BAPPEDA and BPBD. Fourth, Communication is not only carried out at the sub-district level or not only in the PRB forum, but there is advocacy and communication carried out by the Communication and Advocacy sector related to regulations that can be applied and the basis of regulations that can support the increase in Village/Sub-district Resilience Assessment. Fifth, The solution offered by DESTANA is: able to facilitate and support efforts to foster and increase awareness of a sense of alertness to disasters. Participation and Cooperation in the community are expected to form resilience in facing disasters through the formation of Disaster Resilient Villages and ultimately give birth to Disaster Resilient Families (KATANA). Sixth, The activities that have been implemented serve to increase the capacity of coastal communities in 6 DESTANA sub-districts.